Predicting crack spacing of reinforced concrete tension members using strain compliance approach with debonding - Kaklauskas, Gintaris; Ramanauskas, Regimantas; Ng, Pui-Lam (Journal of Civil Engineering and Management, 2019)
A novel technique based on strain compliance for investigating the crack spacing of reinforced concrete (RC) tension members has been developed. The new method is based on the mean strain and the partial interaction (stress-transfer) approaches. The strain compliance principle is established by equating together the mean strains of a reinforced concrete block between adjacent primary cracks estimated by the mean strain and the stress-transfer approaches. The distribution of reinforcement strains within the RC block must be known to apply the stress-transfer approach. This technique is intended for the stabilized cracking stage, where formation of new primary cracks has ceased. This work accounts for local effects – fully damaged bond between the concrete and reinforcement near the cracks. Knowledge of a benchmark data point obtained from a reference element is required. The point is defined by the reinforcement ratio, bar diameter and mean crack spacing values. This data point enables the estimation of the mean crack spacing for other RC tension elements. A comparative investigation was carried out, with two different mean strain approaches, following the free-of-shrinkage tension stiffening law and provisions in Eurocode 2. The obtained results provide reasonably accurate estimates of crack spacing compared to experimental values.